2023
DOI: 10.3390/met13020188
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Imaging of Al6061 Prepared by Solid-State Friction Stir Additive Manufacturing

Abstract: Solid-state Friction Stir Additive Manufacturing has recently gained attention as a result of its capacity to fabricate large-scale parts while preserving the mechanical properties of the feedstock material. However, the correlation between the quality of layer-by-layer bonding of the deposited metal and processing parameters has remained unknown. Neutron imaging techniques, with 90% total transmission per cm, are employed for Al6061 parts fabricated by MELD® Technology as a non-destructive evaluation approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For AFSD, the layer boundaries are formed differently from a regular layer-by-layer printing because of re-stringing of the previous layer [29,31]. Saber et al investigated the layer-by-layer architecture of distinct segments within as-built AA6061 parts created via the AFSD process, employing neutron imaging techniques as a non-destructive evaluation methodology [30]. Their observations indicated that the graphite coating, employed as a dry lubricant on the feedstock's surface, exhibited a tendency to segregate between layers.…”
Section: The Effect Of Test Specimen Directionmentioning
confidence: 99%
See 2 more Smart Citations
“…For AFSD, the layer boundaries are formed differently from a regular layer-by-layer printing because of re-stringing of the previous layer [29,31]. Saber et al investigated the layer-by-layer architecture of distinct segments within as-built AA6061 parts created via the AFSD process, employing neutron imaging techniques as a non-destructive evaluation methodology [30]. Their observations indicated that the graphite coating, employed as a dry lubricant on the feedstock's surface, exhibited a tendency to segregate between layers.…”
Section: The Effect Of Test Specimen Directionmentioning
confidence: 99%
“…Aluminum alloys, known for their lightweight nature, possess exceptional strength-to-weight ratios, as well as remarkable resistance to corrosion [28]. Notably, the literature has documented the successful utilization of AFSD in the manufacturing of AA6061 [19,29,30], AA2050 [31], AA2011 [32], AA2024 [13], AA2219 [33,34], AA5083 [35,36], AA5B70 [37], and AA7075 [24,[38][39][40][41] parts, showcasing the versatility and potential of this technique for aluminum alloy processing. The deposition of parts made of other metal alloys is also reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation